Transport at the air-dea interface: measurements, models and parametrizations - Garbe, Christoph S.; Handler, Robert A.; Jähne, Bernd (Environmental Science and Engineering, Environmental Science, 2007)
One key uncertainty in predictions of future climate is caused by the lack of knowledge of transport processes in the air-water interface; this poses the main transfer resistance between oceans and atmosphere. This book reviews recent progress in the domains of experimental process studies as well as computer stimulation. It represents an early approach of merging insights gained in both fields and broadens our understanding of air-water gas and heat exchange.